2007
DOI: 10.1002/edn.73
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peer-group support and problem-solving training in the treatment of adolescents with type 1 diabetes

Abstract: Aim: The aim of this study was to describe the elements and results of peer-group support and problem-solving training in the treatment of adolescents with type 1 diabetes and their parents. The hypothesis was that the intervention would improve HbA 1c and enable the adolescents to take responsibility in managing their diabetes. Method: A total of 60 adolescents with type 1 diabetes, aged 13-18 years, and their parents, were invited to participate in this study. They were recruited from outpatient clinics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 117 publications
0
21
0
Order By: Relevance
“…Three (13%) studies [9,16,17] examined only females and 2 (8%) studies did not report gender [21,30], but the rest of the studies included both genders. Race/ethnicity of study participants was not reported in 3 (13%) studies [18,22,31]. One study examined Caucasians [32], 12 (50%) studies included multiple ethnicities (generally Caucasian, African American, and Latino)[7,11,12,14-16,19,21,23,25,26,30], 5 (21%) studies were African American only [8,9,20,27,28], 2 study samples were Latino[13,17], and 1 study sample was South Korean [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three (13%) studies [9,16,17] examined only females and 2 (8%) studies did not report gender [21,30], but the rest of the studies included both genders. Race/ethnicity of study participants was not reported in 3 (13%) studies [18,22,31]. One study examined Caucasians [32], 12 (50%) studies included multiple ethnicities (generally Caucasian, African American, and Latino)[7,11,12,14-16,19,21,23,25,26,30], 5 (21%) studies were African American only [8,9,20,27,28], 2 study samples were Latino[13,17], and 1 study sample was South Korean [24].…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies of children and adolescents, five (71%) [7,11,21-23] were randomized controlled trials and the remaining two were quasi-experimental designs [31,32] (Table 2). In five (71%) of the intervention studies problem-solving was the main behavioral treatment approach, [7,11,21,22,31] and in two studies problem solving was combined with Behavioral Family Systems Therapy [23] or Cognitive Behavioral Therapy [23,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two domains of outcome measures were extracted: diabetes functioning/medically performing/HbA1c and psychosocial functioning. Studies were excluded if they involved improving education alone, had no explicit theoretical background, 6,7,[44][45][46] were not a RCT, 15,[46][47][48][49][50] included children only 51,52 or adults 53 54 ) were checked in order to capture other relevant publications (see Appendix A for search terms at www.bjd-abcd.com).…”
Section: Eligibility Criteriamentioning
confidence: 99%